(untitled) (Texas Journal of Multidisciplinary Studies, 2023)
: In an increasingly competitive global landscape, individuals must adopt and integrate the four Cs, namely collaboration, communication, creativity, and critical thinking, into their learning endeavors. In the present era of education, it is imperative to adopt effective strategies that enhance essential life skills, foster active student participation, and are grounded in rigorous research, all while promoting critical thinking. This essay aims to highlight the substantial influence that literature may have in English as a foreign language (EFL) settings while considering the four Cs. In a broad sense, a literature-based program can derive three significant advantages. The objectives encompassed in this context include expanding students’ understanding of literature to foster aesthetic appreciation, showcasing a diverse array of principles explored in substantial literary works, and facilitating the development of various facets of foreign language proficiency. Therefore, it is imperative to prioritize literature-related experiences in contemporary schooling. Section Two presents some justifications for incorporating literature in English as a Foreign Language (EFL) setting. Section Three of the paper examines several studies carried out in the context of the English as a Foreign Language (EFL) classroom. Section Four of the document delineates a range of activities and tactics that can be employed to underscore the importance of high-quality instruction in analyzing and interpreting literary passages. Section Five of the paper outlines the criteria the author has put out to select literary works in English as a Foreign Language (EFL) contexts. Finally, Section Six culminates by presenting a series of recommendations that EFL specialists should consider